Nursing professional Performance in Urgency and Emergency Units (Research, Society and Development, 2022)
With the emergence of the new health problems, increased the search for attendance and hospitalizations in urgency and emergency services, where the nurses experience day by day numberless cases of situacions who lack atencion, care and quickness during the provision of assistance. Therefore, this study aims to evidence the nurse professional actuation active in urgency and emergency unit. It is about a systematic literature review, with a qualitative approach, through the search in the databases “Medical Literature Analysis and Retrieval System Online” and “Nursing Database in the Virtual Health Library”, with the use of descriptors in health science in association with the “AND”, researching as follows: “Role AND Nurse AND Urgency AND Emergency”. In the study was taken in consideration the perception by the own nurses, it is understood that the duties involve minimizing the users waiting time with the opportune attendance and based on needs, giving priority to the who found in worst state, the safe decision making, autonomy, knowledge and quickness, always looking for patient satisfaction. We concluded that the nurse usually assumes the role of a leader inside of the urgency and emergency unity. Acting since the use reception, with the welcome and the qualified listening, acts on part practice-assistance, performing the exclusive functions of their category, but also assists during the cares with others professionals, In addition to acting as a manager, organizing the sector, the team and the all logistics that involves the urgency and emergency sector.